PROFIL TENAGA KERJA PEREMPUAN DI SEKTOR USAHA KECIL MENENGAH (Studi Pada Tenaga Kerja Perempuan UKM Konveksi Di Kota Semarang) - Rodhiyah Rodhiyah (Jurnal Administrasi Bisnis, 2013)
This study aims to determine the factors driving women working in SMEs convection sector and those working women’s contribution to family income. This study used a descriptive qualitative approach through in-depth interview. The research found that reasons to work are economic factor, because the husband works as a laborer and cannot meet their daily needs, the women may help meeting their family needs by working, productive spare time, and also socializaton with friends. The reasons to work at SMEs convection are the company’s nearby location, comfortable working environment, lenient rules and minimum penalties, easy permit to take a day off, not early starting working hours, and friendly small business owners. It is recommended that female workforce increase their knowledge and skills and improve their productivity by being more diligent and motivated. SMEs must provide salary that meets the minimum wage standard and give proper overtime pay. To avoid delay in providing raw materials, it is necessary to have technicians and give production benefits.